2020
DOI: 10.1186/s12904-020-00542-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, barriers to physical activity and predictors for motivation to exercise in advanced Cancer patients

Abstract: Background: In order to counteract fatigue, physical activity (PA) is recommended for all stages of cancer. However, only few advanced cancer patients (ACP) are physically active. Quantitative data with high numbers of ACP reporting barriers to PA are missing. This study aimed to identify barriers to PA in ACP with tiredness/weakness and investigate their motivation towards it. Methods: Outpatients with metastatic cancer receiving cancer care at a German Cancer Center reporting moderate/severe tiredness/weakne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 46 publications
6
51
0
2
Order By: Relevance
“…Studies revealed that cancer and its related treatment’s side effects acted as a significant physiological barrier to PA participation among patients across cancer types and treatment stages (Table 4 ). In five cross-sectional studies, about 70–80% of mixed cancer patient participants at different treatment stages reported that cancer therapy-related adverse effects hindered their PA engagement [ 18 , 20 , 21 , 25 , 48 ]. The most common and significant side effects reported by mixed cancer patients were fatigue, gastrointestinal issues and joint pain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies revealed that cancer and its related treatment’s side effects acted as a significant physiological barrier to PA participation among patients across cancer types and treatment stages (Table 4 ). In five cross-sectional studies, about 70–80% of mixed cancer patient participants at different treatment stages reported that cancer therapy-related adverse effects hindered their PA engagement [ 18 , 20 , 21 , 25 , 48 ]. The most common and significant side effects reported by mixed cancer patients were fatigue, gastrointestinal issues and joint pain.…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent co-morbidities reported by cancer patients included arthritis, diabetes and heart disease. Cross-sectional studies by Bluethmann et al [ 121 ] and Frikkel et al [ 18 ] showed that comorbidity was a significant negative predictor of PA levels among mixed cancer patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue is the most frequent adverse event reported in cancer patients with over 90% [ 3 ] and has been shown to be a consequence of active treatment, but it may also persist long term into post-treatment periods [ 4 ]. To improve fatigue the National Comprehensive Cancer Network guidelines recommends non-pharmacological interventions such as physical activity (PA) for all stages of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the influence of PA was assessed and highlighted as a possible approach to improve patients QoL [ 12 , 13 ]. Despite the benefits, lack of motivation, physical symptoms, fatigue and lack of time are often barriers to PA [ 3 , 14 ]. Therefore, it is highly important to develop interventions that are feasible and empower the patients to adhere to recommendations of PA. An important concept in the empowerment of patients is the model of self-efficacy [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%